2022
DOI: 10.1093/scan/nsac058
|View full text |Cite
|
Sign up to set email alerts
|

Social goals in girls transitioning to adolescence: associations with psychopathology and brain network connectivity

Abstract: The motivation to socially connect with peers increases during adolescence in parallel with changes in neurodevelopment. These changes in social motivation create opportunities for experiences that can impact risk for psychopathology, but the specific motivational presentations that confer greater psychopathology risk are not fully understood. To address this issue, we used a latent profile analysis to identify the multidimensional presentations of self-reported social goals in a sample of 220 girls (9-15 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…It is worth noting that our particular multilayer implementation, and by extension our layer-based analysis, can be applied to any set of interrelated measures. Our application of multilayer modeling to perceived social support is motivated by work in neuroecology (Gonzalez et al, 2015; Coan et al, 2017; Pelletier-Baldelli et al, 2022; DeCross et al, 2022; Morawetz et al, 2020), but the implementation’s agnosticism toward the measures used speaks to its generality: it is a powerful tool for a wide variety of research questions. This approach can be used to investigate how brain connectivity varies across experiences in the physical or economic environment or across different behavioral or cognitive measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that our particular multilayer implementation, and by extension our layer-based analysis, can be applied to any set of interrelated measures. Our application of multilayer modeling to perceived social support is motivated by work in neuroecology (Gonzalez et al, 2015; Coan et al, 2017; Pelletier-Baldelli et al, 2022; DeCross et al, 2022; Morawetz et al, 2020), but the implementation’s agnosticism toward the measures used speaks to its generality: it is a powerful tool for a wide variety of research questions. This approach can be used to investigate how brain connectivity varies across experiences in the physical or economic environment or across different behavioral or cognitive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Because the HCP dataset includes only adults, we were limited in the developmental conclusions we can draw. Bigger effect sizes would be expected in adolescent populations in particular, since adolescent represents a critical period of rapid and high-stakes adaptation to the (especially social) environment (Rudolph et al, 2021; Gonzalez et al, 2015; Pelletier-Baldelli et al, 2022; DeCross et al, 2022). Applying methods similar to ours to a dataset like that of Adolescent Brain Cognitive Development study may be particularly illuminating.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 99 participants included in primary analyses, approximately 58% self-reported that they had experienced menarche. A portion of this sample has been analyzed in one prior study using the same fMRI task ( Pelletier-Baldelli et al, 2023 ); this prior study focused on identifying social goals and associated brain connectivity, with no attention to puberty and age links with brain function. Participants' assent and caregiver consent was obtained according to the Declaration of Helsinki, and all consent and study procedures were pre-approved by the University’s Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Brain function was examined using a social evaluation fMRI task ( Miller et al, 2019 , Pelletier-Baldelli et al, 2023 , Somerville et al, 2013 ). Participants were told that the task examined how their brains responded to an initial interaction with a similar aged, same-sex peer.…”
Section: Methodsmentioning
confidence: 99%